Left ventricular systolic and diastolic function in severe obesity: a radionuclide study - Ferraro, S; Perrone-Filardi, P; Desiderio, A; Betocchi, S; D'Alto, M; Liguori, L; Trimigliozzi, P; Turco, S; Chiariello, M (Cardiology, 1996)
To verify the impact of sever obesity (defined as body mass index > 31 kg/m2) on left ventricular (LV) function, 32 asymptomatic obese but otherwise healthy subjects (16 men; age 38 +/- 11 years) voluntarily underwent first-pass and equilibrium 99mTc radionuclide angiography at rest and, in 22 of them, during bicycle supine exercise. Data were compared to those obtained from 10 normal volunteers (age 48 +/- 13; p < 0.05, vs. obeses). End-diastolic and stroke volumes did not differ between the two groups, whereas end-systolic volume was significantly higher in obese subjects (67 +/- 20 vs. 49 +/- 20 ml; p < 0.05), and, as a consequence, LV ejection fraction at rest was decreased in obese subjects (59 +/- 7%) compared to normals (65 +/- 6%; p < 0.05). Due to the higher heart rate in obese subjects (81 +/- 13 vs. 69 +/- 10 pbm, respectively; p < 0.05) cardiac output was significantly greater compared to normals (7.1 +/- 0.8 vs. 6.2 +/- 0.2 liters/min, respectively; p < 0.01). During exercise, ejection fraction normally increased in normals (70 +/- 7%; p < 0.001, vs. baseline) but not in obese subjects (60 +/- 9%; p = nonsignificant vs. baseline). In addition, systolic blood pressure/end-systolic volume ratio was significantly decreased in obese subjects (23 +/- 1.3) compared to normals (2.8 +/- 1.6; p < 0.05). Peak filling rate, normalized to end-diastolic counts per second, was significantly lower in obese subjects (2.2 +/- 1.3) compared to normals (2.8 +/- 1.6; P < 0.05). This difference was also true when peak filling rate was computed in stroke counts per second (3.8 +/- 0.8 in obeses vs. 4.4 +/- 0.4 in normals; p < 0.05). Repeat analysis in a subgroup of 10 young obese subjects (age < or = 30 years) confirmed decreased ejection fraction at rest (60 +/- 4%; p < 0.05) and peak filling rate (2.4 +/- 0.4 end-diastolic counts/s; p < 0.05), as well as the lack of ejection fraction increase during exercise (59 +/- 9%). Thus, these data indicate a subclinical impairement of LV systolic and diastolic function at rest and during exercise in asymptomatic severely obese but otherwise healthy subjects.